Pembentukan Pokdarwis Serta Pendampingan Prosedur Keselamatan Kerja dalam Pengelolaan Wisata Perahu di Kelurahan Degayu Kota Pekalongan - Jaya Maulana; Dwi Edi Wibowo (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) AMIK Indonesia, 2023)
Degayu Village is one of the areas affected by tidal floods in North Pekalongan District. Most of the rice fields of the residents of Degayu Village are currently submerged by 1-1.5 meters of tidal water which has forced some residents to change their profession from farmers to fishermen, anglers, fishing net craftsmen, and so on. However, with their new jobs, many residents find it difficult to adapt, resulting in a decrease in family income. For this reason, the Kelurahan government is trying to take advantage of the rice fields that have been submerged in water to become a potential for boat tourism so that economic growth can improve again. The tours offered are boat tours along the water while enjoying the natural scenery of the north coast. However, the results of in-depth interviews with several informants as well as direct observation of the location found the following problems; there are no work safety standards or procedures for boat tourism, for example, there are no life jackets and personal protective equipment for boats passengers and drivers, there is no rescue team in the event of an accident, no first aid facilities are available, and there is no tourism awareness group that manages the tourism potential properly. Well, besides the potential for boat tourism, there are also many other potentials that can be maximized, such as floating culinary tours, water bikes, mangrove parks, and so on. For this reason, it is necessary to form a tourism awareness group that is trained in tourism management both from an economic and work safety perspective.